2007
DOI: 10.1161/atvbaha.107.147918
|View full text |Cite
|
Sign up to set email alerts
|

The Problem of Passenger Genes in Transgenic Mice

Abstract: Abstract-Gene targeted or transgenic mice are frequently created on one genetic background and the mutation then transferred to a second genetic background by a series of backcrosses, with selection for the mutation at each generation. This is the same experimental design as that used in the production of classical congenic strains in which a genomic region from a "donor" strain is transferred to the background of a "recipient" strain by backcrossing and selection for ten or more generations. While the strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 25 publications
0
70
1
Order By: Relevance
“…In addition to encoding proteins performing a wide diversity of functions (see below), the regulated genes in both Cx43 KO and SI astrocytes were located on all chromosomes as presented in Figure 2A. This lack of association of altered genes with a particular chromosome indicates that effects of both knockdown and knockout are not due to bystander effects related to chromosome location (see Cajiao et al, 2004) or "passenger effects" of the transgene construct (see Lusis et al 2007). …”
Section: Gene Expression Regulationmentioning
confidence: 98%
“…In addition to encoding proteins performing a wide diversity of functions (see below), the regulated genes in both Cx43 KO and SI astrocytes were located on all chromosomes as presented in Figure 2A. This lack of association of altered genes with a particular chromosome indicates that effects of both knockdown and knockout are not due to bystander effects related to chromosome location (see Cajiao et al, 2004) or "passenger effects" of the transgene construct (see Lusis et al 2007). …”
Section: Gene Expression Regulationmentioning
confidence: 98%
“…The fi rst study showed a signifi cant association between cholesterol effl ux from human skin fi broblasts and increased carotid intima media thickness (cIMT; a surrogate endpoint for cardiovascular endpoints) in nine individuals (49). The second study, of 142 subjects undergoing coronary angiography, showed correct interpretation diffi cult (79). The wide-spread use of cholate-containing atherogenic diets, especially in that period, causing liver toxicity and gall stone formation, further complicates matters (80).…”
Section: Other Potentially Atheroprotective Propertiesmentioning
confidence: 99%
“…Genetargeted mice are usually initially created on one of the many substrains of 129 mice, and the null mutation subsequently transferred into C57BL/6 (B6). Thus, unless separated by recombinations, the region flanking the targeted gene from 129 will be carried with the targeted gene (2). This can lead to incorrect conclusions if allelic differences between 129 and B6 affect HDL.…”
mentioning
confidence: 99%